Development of Training Model Through Media Images in The Form of Pocketbook Taekwondo Kick Technique for Beginners - Metidesiana Metidesiana; Iyakrus Iyakrus; Hartati Hartati; Arisman Arisman (Universitas PGRI Palembang, 2021)
This research aims to develop an exercise model through image media in the form of pocketbook taekwondo kick techniques forbeginners. The method used is Research and Development. Research site at Club Taekwondo Court Palembang. The subjects in this study were taekwondo novice participants in the District Court with a total of 30 people with the technique of taking research subjects using purpose sampling techniques. The results showed that validation of the development of the training model through the image media in the form of pocketbook taekwondo kick technique for beginners is validator I with a percentage of 98%, validator II with a percentage of 96%, and validator III with a percentage of 96%, thenthe pocket book developed is worth using on kick techniques for taekwondo beginners. The reliability rate in small group trials is 0.988 and large group trials are 0.998, so it can be categorized as high reliability level. Overall, the development of learning models for taekwondo novice participants is helpful in remembering or reinvigorating material about taekwondo kick techniques, attractive design and easy-to-understand images make taekwondo novice participants easy to practice movement, and practical pocketbooks to carry around.